2019
DOI: 10.1093/mnras/stz2697
|View full text |Cite
|
Sign up to set email alerts
|

The C-Band All-Sky Survey (C-BASS): Simulated parametric fitting in single pixels in total intensity and polarization

Abstract: The cosmic microwave background B-mode signal is potentially weaker than the diffuse Galactic foregrounds over most of the sky at any frequency. A common method of separating the CMB from these foregrounds is via pixel-based parametric-model fitting. There are not currently enough all-sky maps to fit anything more than the most simple models of the sky. By simulating the emission in seven representative pixels, we demonstrate that the inclusion of a 5 GHz data point allows for more complex models of low-freque… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…In the case of the CP(L) set, we struggle to place accurate constraints on the synchrotron spectral index. This is to be expected, given the lack of low-frequency channels below 40 GHz, and is consistent with expectations from the single-pixel component separation analysis presented in Jew et al (2019). For the CP(LC) validation set, we are able to place improved constraints on the synchrotron spectral index, with the variations in the synchrotron spectral index from region-to-region tracing the variations in the input spectral index map shown in Fig.…”
Section: Synchrotron Spectral Parameterssupporting
confidence: 87%
See 4 more Smart Citations
“…In the case of the CP(L) set, we struggle to place accurate constraints on the synchrotron spectral index. This is to be expected, given the lack of low-frequency channels below 40 GHz, and is consistent with expectations from the single-pixel component separation analysis presented in Jew et al (2019). For the CP(LC) validation set, we are able to place improved constraints on the synchrotron spectral index, with the variations in the synchrotron spectral index from region-to-region tracing the variations in the input spectral index map shown in Fig.…”
Section: Synchrotron Spectral Parameterssupporting
confidence: 87%
“…Given the simulated data sets considered here, fitting foreground spectral parameters with any parametric method will ultimately be limited by the number of frequency channels available with sufficient sensitivity. For example, in Jew et al (2019), it was found that to constrain models including the synchrotron curvature would require additional low-frequency channels between 5 and 30 GHz. Given a maximum observed frequency of ∼400 GHz, dust spectral parameters in the modified blackbody (MBB) model are also very poorly constrained Jew et al 2019).…”
Section: I F F U S E C O M P O N E N T M O D E L Smentioning
confidence: 99%
See 3 more Smart Citations